STRENGTHENING HEALTH LITERACY AS THE MAIN PILLAR OF REALISING HEALTHY SCHOOLS AT NAHDLATUL ULAMA JUNIOR HIGH SCHOOL IN BANJARMASIN CITY - Unja, Ermeisi Er; Dias, Maria Frani Ayu Andari; Tutpai, Gertrudis (Community Service Journal of Indonesia, 2024)
Strengthening health literacy in realising healthy schools is one of the focuses of community service activities to be achieved in this activity. Gerakan Sekolah Sehat (GSS) is an activity programme that aims to improve the health and well-being of students in the school environment. This programme covers a wide range of aspects, from improving the cleanliness of the school environment to health education for students at school. Some of the main components of the healthy school movement include health education, provision of health facilities and waste management. Along with the implementation of this PMP activity, it is hoped that the data will help to overcome some of the existing shortcomings. The participants in this counselling and training activity were 25 UKS cadres consisting of 20 students and 5 accompanying teachers. Thefirst activity carried out was the socialisation of the role of the UKS cadres as well as the duties and responsibilities of the UKS cadres. Furthermore, training on clean and healthy living behaviour (PHBS) and first aid for accidents (P3K) was conducted. The second activity is to revitalise the UKS room. The UKS room will be organised according to its function. Incomplete UKS equipment will be tried to be equipped in accordance with the actual UKS standards. The third activity is the implementation of counselling and socialisation on how to prevent 3 major sins to partners and UKS cadres. At the evaluation stage, data on the increase in knowledge was obtained as much as 80% in the good knowledge category and the results of observations showed that the cadres could carry out health checks using tools independently.